“Las tic en el aprendizaje autónomo de la asignatura de matemática” - Cruz Lagos, Guadalupe Susana (2023)
Nowadays, education demands the incorporation of TIC in the didactic process, since they have been acquiring an increasing importance and evolving over the last years, therefore, it is necessary to use innovative resources that motivate students to learn mathematics. It should be added that mathematics is considered to be a difficult subject to understand, to which most students put resistance in learning. Therefore, traditional resources do not respond to the needs of the students of the present century, since they focus only on traditional, memoristic and monotonous learning. In addition, there is a lack of teacher training in the use and management of technological tools, therefore, educators should be oriented on the proper use of audiovisual resources, which allow the development of autonomy to learn and mathematical logical reasoning. Therefore, the objective of the research is to strengthen the design and application of audiovisual resources for the improvement of autonomous learning of mathematics in students of the eighth grade of basic education of the educational unit "Alejandro Dávalos Calle". The methodology used for the development of this project is framed in qualitative research because it allows understanding the reality of the educational context, field research was also used for data collection. The method used in this work is the inductive method. The technique used was observation, with its instrument the observation guide that allowed obtaining information from the subjects of the research of the educational unit for the elaboration of audiovisual resources. The results of the research are the creation of a more creative and dynamic educational space, which is based on the application of functional and practical audiovisual resources that will support the development of the class. The research will contribute to educational innovation in order to apply new digital didactic tools that will serve to develop autonomous learning in students, in such a way that it will capture the attention, interest and motivation of the student and will generate improvements in the learning of mathematics.